Effects of municipal solid waste incineration fly ash on the characterization of cement-stabilized macadam. (20th May 2019) - Yan, Kezhen; Gao, Fengqian; Sun, Hao; Ge, Dongdong; Yang, Shu
Highlights: Cement stabilized macadam with MSWI fly ash was partial replacement of cement. Mechanical properties of CSM containing MSWI fly ash were determined. Dry shrinkage and freeze-thaw tests were performed. The suggested maximum dosage of MSWI fly ash in CSM was determined. Abstract: In order to investigate the influence of municipal solid waste incineration (MSWI) fly ash on the characterization of cement-stabilized macadam (CSM), MSWI fly ash was studied as a potential partial substitute for Portland cement. CSM was prepared by adding 0%, 25%, 50% and 75% MSWI fly ash to replace cement so as to find the suggested maximum dosage of MSWI fly ash. The laboratory performance of CSM with MSWI fly ash was evaluated, which includes compressive strength, compressive resilience modulus, splitting strength, dry shrinkage and freeze-thaw resistance. The results concluded that. addition of MSWI fly ash had. positive influence on. the characterization of CSM. The mechanical properties of CSM containing MSWI fly ash was enhanced by increasing curing time. However, the strength of. CSM was decreased with the increase. of MSWI fly ash. content. The compressive resilience modulus, splitting strength and 7d compressive strength. of CSM containing 25% MSWI fly ash met the specifications of the CSM base course as set by the Chinese Standard. The dry shrinkage property of CSM can be ameliorated by containing MSWI fly ash. The residual compressive. strength ratio of CSM after freeze-thaw cycles decreased. with increasing MSWI fly ash content. The concentration of investigated elements in leachates was obviously lower than the restriction of the Chinese Standard. By partially replacing cement with MSWI fly ash. in the CSM, the heavy metals leaching related issues can be relieved. About 25% MSWI fly ash content (<50%) was the suggested maximum dosage of CSM containing MSWI fly ash.